Delays in the decision to seek care and associated factors among mothers who delivered in rural health centers in Wolaita Zone, Southern Ethiopia - Gelaw, Kelemu Abebe; Atalay, Yibeltal Assefa; Zerefu, Firehiwot; Gebeyehu, Natnael Atnafu (Frontiers in Global Women's Health, 2024)
Background Delays in seeking care in health facilities during pregnancy and childbirth can potentially lead to adverse outcomes for women with obstetric complications. These complications lead to maternal mortality and morbidity in developing countries such as Ethiopia. The magnitude and underlying causes of maternal first delay in Ethiopia, particularly in rural areas of the country, are not well documented. This study aims to assess the magnitude of delay in the decision to seek care and associated factors among mothers who gave birth in rural health centers in Wolaita Zone, Southern Ethiopia. Method and materials A facility-based cross-sectional study was undertaken among mothers who gave birth in rural health centers of Wolaita Zone, Southern Ethiopia, from 30 June 2020 to 30 July 2022. A sample size of 410 study participants was selected from each public health center using the systematic random sampling method. Data were collected from a pretested and structured questionnaire using an Open Data Kit; analysis was carried out using SPSS version 25. The determining factors for the first delay were identified using binary logistic regression. Variables with a p-value of less than 0.25 in binary analysis were selected for a multivariable analysis. Variables with a p-value of less than 0.05 were considered statistically significant. Results The magnitude of delay in the decision to seek care in health facilities was 42.1% among mothers who gave birth in rural health centers in the Wolaita Zone, Southern Ethiopia. Unemployed mothers (Adjusted Odd Ratio, 2,529; 95% CI, 1.546, 4.136), husbands with no formal education (Adjusted Odd Ratio, 1.290; 95% CI, 1.029, 1.616), mothers who had negative attitudes towards seeking care in health facilities, and (Adjusted Odd Ratio; 1.695; 95% CI, 1.061, 2.709) were significantly associated with a delay in the decision to seek care at a health facility. Conclusion The magnitude of the first maternal decision to seek care at health facilities among mothers was high in the study area. Efforts should be made to strengthen the literacy level of the husbands of mothers and increase household income through various income-generating approaches. In addition, the dissemination of health information could effectively raise community awareness of the importance of institutional delivery.